Can consumer complaints reduce product reliability? Should we worry? - Coleff, Joaquín (2013)
We analyze a monopolist’s pricing and product reliability problem when consumers are entitled to product replacement but have heterogeneous cost of exercising this right, and we assess the implications of a decrease in consumers’ claiming cost on reliability, profit, and welfare. We find that reducing consumers’ claiming cost may reduce reliability and increase profit. Additionally, the model can explain why some firms encourage consumers to complain while others discourage consumers from complaining. We also show that welfare and profit are partially aligned, specially when consumers’ claiming cost are relatively low and the firm prefers to promote complaints; consequently, we find that encouraging complaints will eventually increase welfare.